O ambiente interagências nas operações de pacificação do Complexo da Maré - Pereira, Fabio da Silva (2016)
The aim of this study is realize an interaction analysis between Brazilian Army and the 42 (forty-two) military and civilian agencies in Maré slums and how these influence the doctrine of military pacification operations. Operation San Francisco - started on April 5, 2014 by Force Pacification (F Pac), was assigned to the Ministry of Defense components to ensure and promote the guarantee of law and order (GLO) public in the Complexo da Maré communities, in Rio de Janeiro city. The proposed methodology is based on applied research with mixed approach technique, through literature, analyzing the documents and reports of F Pac and interviews to members of the military and civil forces that provide public services in the aforementioned region. For this, we used the inductive method by means of statistical tests, to identify causal relationships between the demands of civil utilities met in the communities as well as their influence in the peace operations and defense policies in aimed at updating of doctrine and of military operations. The expected theoretical contributions are the observation of changes in operational use in an environment with high crime and low Human Development Index (IDH) and provide information for collaborative work and all civil institutions under the military protection (but not under military control). This aims to provided the population with access to basic public services safely and minimized wear of GLO actions through the achievement of local public opinion. Expected practical contributions reside in increasing the purely military potential, promoting the adoption of effective public policies civil folders. The implications relate to the approach and more interaction between the military government and civil folders through the mediation of the Section of Civil Affairs. The researches of this work are evident as they are restricted to the context of the pacification of a set of slums in the state capital of Rio de Janeiro in 2014